COVID-19-Associated Pulmonary Aspergillosis in Intensive Care Unit Patients from Poland - Magdalena Skóra; Mateusz Gajda; Magdalena Namysł; Jerzy Wordliczek; Joanna Zorska; Piotr Piekiełko; Barbara Żółtowska; Paweł Krzyściak; Piotr B. Heczko; Jadwiga Wójkowska-Mach (Journal of Fungi, 2023)
Coronavirus disease 2019 (COVID-19) has been shown to be a favoring factor for aspergillosis, especially in a severe course requiring admission to the intensive care unit (ICU). The aim of the study was to assess the morbidity of CAPA among ICU patients in Poland and to analyze applied diagnostic and therapeutic procedures. Medical documentation of patients hospitalized at the temporary COVID-19 dedicated ICU of the University Hospital in Krakow, Poland, from May 2021 to January 2022 was analyzed. In the analyzed period, 17 cases of CAPA were reported with an incidence density rate of 9 per 10 000 patient days and an incidence rate of 1%. Aspergillus fumigatus and Aspergillus niger were isolated from lower respiratory samples. Antifungal therapy was administered to 9 patients (52.9%). Seven patients (77.8%) received voriconazole. The CAPA fatality case rate was 76.5%. The results of the study indicate the need to increase the awareness of medical staff about the possibility of fungal co-infections in ICU patients with COVID-19 and to use the available diagnostic and therapeutic tools more effectively.